ETHICS AND POLITICS IN lEAN JACQUES ROUSSEAU - Almada, Javier (2008)
The article focuses on the way ethics and politics are put together in Rousscau's works.His views about man's morals, his hypothesis about the natural man and how he !cavesthe natural state, the making of civil society, the establishment of a social contraer, thcgeneral will as sovereign, laws, legislation, and government, are given consideration.